An asymmetrical jaw can cause a lot of problems - Abu Bakar, Noraini (Star Media Group Berhad, 2018)
Orthognathic surgery or corrective jaw surgery is a method of treatment that may be advised for patients who have severe jaw size problems, including asymmetry.